Antibiotic susceptibility pattern of Staphylococcus epidermidis - Haque, Nazia; Hossain, MA; Bilkis, L; Musa, AK; Mahamud, C; Bari, MS; Haque, N; Muhammad, N; Parvin, US; Islam, MT; et al. (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):142-7. The abstract of this article is available on the PubMed website